Sensory and physico-chemical analysis of roasted marama beans [Tylosema esculentum (Burchell) A. Schreiber] with specific focus on compounds that may contribute to bitterness - De Kock, Henrietta Letitia (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2014.